Multicultural education based on local wisdom in the perspective of civic education through the Nguras Enceh tradition - Rahmawati, Elly Nur; Sutrisno, Cucu; Fianisa, Rizka (Jurnal Civics: Media Kajian Kewarganegaraan, 2024)
Multicultural education is a critical issue in increasingly heterogeneous modern societies. Multicultural values must be instilled early to build understanding, appreciation, and positive attitudes towards cultural diversity. One effective approach is to explore local wisdom within communities. This qualitative case study examines the multicultural values embedded in the Nguras Enceh tradition at the Mataram Kings' Cemetery Complex in Imogiri, representing a unique form of local wisdom in Yogyakarta. Data were collected through participant observation, in-depth interviews, and documentary studies during the Nguras Enceh tradition. From the perspective of citizenship education, the values of togetherness, cooperation, tolerance, and respect for diversity in the Nguras Enceh tradition serve as important assets for instilling multicultural attitudes and national identity among the younger generation. This research demonstrates that the Nguras Enceh tradition is not merely a cultural heritage but also contains noble values that align with efforts to strengthen good citizenship following the spirit of multiculturalism and Bhinneka Tunggal Ika (Unity in Diversity). The results of this study underscore the importance of appreciating and preserving local wisdom as a medium for learning multicultural values in the context of citizenship education at local, national, and global levels. Integrating local wisdom into citizenship education curricula can strengthen the inculcation of citizenship values that are more contextual, meaningful, and applicable in students' daily lives.